Everybody's fine [videorecording (DVD)] - Jones, Kirk, 1964-; Beckinsale, Kate; De Niro, Robert; Rockwell, Sam; Barrymore, Drew; McCartney, Paul (Miramax Films, 2010)
When Frank Goode's grown children cancel a family reunion, the recent widower sets off on a cross-country journey to reconnect with each of them. A family separated by physical and emotional distance finds a way to come together.